Color of computer display frame in work performance, mood, and physiological response. - Hatta, Takeshi; Yoshida, Hirotaka (Perceptual & Motor Skills, 2002)
The effects of the color of a personal computer screen on work performance, psychological mood, and autonomic response were investigated. 24 subjects were asked to perform visual tasks presented on the computer display. Three types of computer monitor, which were colored red, blue, or beige, were employed to present visual cognitive tasks. The mood measure, the Japanese Stress Arousal Check List, and heart rate measurement were administered before and after work on each color of computer monitor. Analysis of a low-demand task (Exp. 1) showed that the red computer monitor reduced visual task performance compared to that with the blue, while the blue monitor decreased visual task performance on a high-demand task (Exp. 2). The color of the monitor did not affect mood or heart rate. Based on these findings, the effect of the color of environmental cues on work was discussed. Reprinted by permission of the publisher.